Social life cycle assessment of biomethane production and distribution in Latvia (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
A social life cycle assessment is proposed for the evaluation of the social potential impact in regard to the production and use of biomethane derived from biomass (algae and manure) in Latvia. The Multi-Criteria Analysis (MCA) is used to evaluate the social performances, which have been selected based on literature, statistics and legislation data. Seven alternatives are evaluated by experts and the best alternative is figured out.